Comparative analysis between dynamic hip screw with trochanteric stabilisation plate and dynamic hip screw alone in the management of unstable intertrochanteric femur fractures - Anand, Rajeev; Dwivedi, Amit; Sharma, Anupinder (International Journal of Research in Orthopaedics, 2020)
Background: Intertrochanteric fractures of the femur are difficult to manage because of the complex patterns they present with. A dynamic hip screw (DHS) and a DHS supplemented with a trochanteric stabilisation plate (TSP) are among a variety of fixation methods used in the management of such injuries. We compared the efficacy of DHS with TSP to DHS alone in the treatment of unstable intertrochanteric femur fractures. Methods: 30 patients of intertrochanteric femur fractures (mean age 72 years) were included in the study, 14 were treated using DHS with TSP while 16 were treated using DHS alone, they were followed up till 16 weeks and the progress was recorded according to the parameters in the Salvati and Wilson score. Results: 14 patients were treated using DHS with TSP, 11 of them had excellent Salvati and Wilson scores, 3 patients recorded good scores, 11 patients were able to walk with no pain while 3 needed aids for walking due to pain, normal function was restored in 12 patients while very little restriction was seen in 2 patients Of the16 patients treated using DHS alone, 10 had excellent scores, 6 recorded a good score, 10 patients walked with no pain while 6 needed aids for walking due to pain, normal function was re-stored in 11 patients, very little restriction was seen in 4 patients while 1 patient had restricted nor-mal activity. Conclusions: DHS with TSP appears to provide better fixation and functional outcome in unstable inter trochanteric fractures over DHS alone.